Cross sectional study comparing the conventional method and modified misgav ladach method for caesarean section in Hospital Kuala Terengganu - Hassan, Mohamad Haslan (2007)
Caesarean section is a common obstetrical operation. About fifteen percent of all deliveries in Hospital Kuala Terengganu were by abdominal route. A century ago, Pfannensteil described a low transverse abdominal incision as an alternative to midline incision. Joel-Cohen introduced a new method of opening the abdomen, which was further modified by Dr. Michael Stark. The new technique was called Misgav Ladach technique. The large controlled studies have demonstrated many advantages of this method. However few steps of this technique had brought controversial issues until present time. This has lead to some modifications of the original method. A few studies with a different modification shown a promising result without arises much debate. This study was to compare the effect of modified Misgav Ladach with conventional method on the operating time, blood loss, duration to deliver the baby and complications such as post partum haemorrhage and extended tear in performing caesarean section. One group was operated by modified Misgav Ladach method and the other group by the conventional method. The operations were performed by two different surgeons. Operating time, duration for delivery the baby, amount of blood loss and complications occur in each method. Operating time was not significantly different between two methods with an average of 27.3 minutes in the modified Misgav Ladach method and 32.8 minutes in the conventional method (p=0.055). The amount of blood loss also was not significantly different with 360ml and 416ml (p=0.065) for modified Misgav Ladach and conventional method respectively. The duration for delivery the baby was not significantly different with modified Misgav Ladach took 2. 7 minutes and conventional method took 3.1 minutes (p=0.07). The numbers of case with extended tear were same in both methods (five cases). There was one case of PPH (0.3%) in conventional method and none in modified Misgav Ladach method (p=0.605). The episode of fever on second day of operation also was not significantly different with 4 cases (2.6%) and 3 cases (2.0%) in modified Misgav Ladach method and conventional method respectively. The modified Misgav Ladach method do not offer any advantages over the conventional method. There were no significant different in operative timing, amount of blood loss, duration for delivery the baby and complications either intra or post operatively.